Interaction between components of polymeric light emitting electrochemical cells: A DFT case study for MDMO-PPV/KCF3SO3/PEO system - Galindo, Levy A. [UNESP]; Alves, Gabriel G.B. [UNESP]; Lavarda, Francisco C. [UNESP]; Batagin-Neto, Augusto [UNESP] (Elsevier, 2023)
Polymer light emitting electrochemical cells (PLECs) are organic electronic devices that define interesting alternatives to organic light-emitting devices. However, despite their potential application, some of the basic operational mechanisms involved in their operation are still not completely understood. In this context, here we report a theoretical attempt to unravel some basic aspects on this subject considering a model system based on poly[2-methoxy-5-(3′,7′-dimethyloctyloxy)-1,4- phenylene vinylene] (MDMO-PPV), potassium(I) trifluoromethanesulfonate (KCF3SO3) and polyethylene oxide (PEO). Structural and reactivity properties of the constituents were evaluated via DFT-based electronic structure calculations. Condensed-to-atoms Fukui indexes were estimated via Hirshfeld partition charge to identify preferred sites for PLEC component's interactions. The results suggest that the presence of ionic salt induces significant changes on the semiconducting polymer's electronic properties, which are dependent on the number of salt molecules and their oxidation state, influencing the devices’ charge dynamics (injection and transport), reinforcing previous results obtained for other similar systems.
Keywords: Electronic structure; Polymer-salt interactions; Polymeric light emitting electrochemical cells; Reactivity indexes